2022
DOI: 10.48550/arxiv.2201.12536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated adiabatic passage in cavity magnomechanics

Shi-fan Qi,
Jun Jing

Abstract: Cavity magnomechanics provides a readily-controllable hybrid system, that consisted of cavity mode, magnon mode, and phonon mode, for quantum state manipulation. To implement a fastand-robust state transfer between the hybrid photon-magnon mode and the phonon mode, we propose two accelerated adiabatic-passage protocols individually based on the counterdiabatic Hamiltonian for transitionless quantum driving and the Levis-Riesenfeld invariant for inverse engineering. Both the counterdiabatic Hamiltonian and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[28], where an STA approach based on counter-diabatic driving and unitary transformations to get rid of terms difficult to implement [29] was applied, see also ref. [30]. A detailed comparison will be carried out elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28], where an STA approach based on counter-diabatic driving and unitary transformations to get rid of terms difficult to implement [29] was applied, see also ref. [30]. A detailed comparison will be carried out elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…z (t f ) components and the following relations hold for the final values of the trajectories, see Eq. (30),…”
Section: Construction Of Further Invariantsmentioning
confidence: 99%
“…In recent years, the analogous cavity magnomechanical system has received considerable attention [20,21]. It has been shown that cavity magnomechanics (CMM) has the potential to prepare macroscopic quantum states [22][23][24][25][26][27][28][29][30][31] and nonclassical states of microwave fields [32,33], and it has also promising applications in quantum information processing and quantum technologies [34][35][36][37][38][39][40][41][42][43]. In the CMM, a magnon mode (spin wave) couples to a deformation vibration mode of a ferromagnet (or ferrimagnet) via the magnetostrictive force, and to a microwave cavity mode via the magnetic dipole interaction.…”
Section: Introductionmentioning
confidence: 99%